The impact of climate change, sea-storm events and land subsidence in the Adriatic - Pietro Teatini; Giuseppe Gambolati (Fondazione Eni Enrico Mattei (FEEM), 2000)
The Northern Adriatic coastland comprised between the cities of Monfalcone and Cattolica is characterised by locations of great tourist interest, such as the Venice Lagoon and the Romagna Riviera, and areas with a very precarious environmental setting, such as the Valli di Comacchio and the Po river delta. Therefore the coastal management and the design of new defense works of the littoral have to be made with the utmost care, possibly with the aid of numerical predictions of the coastal morphodynamics and the flood risk analysis of the lowland involved. In the study area land may subside due to sediment natural compaction and subsurface fluid (water and gas) withdrawal. At the same time littoral transport of solid material can contribute appreciably to change the shore morphology. Mean sea level may rise permanently due to global climate change and occasionally due to tides and intensive storm events. The predictions of each individual process are obtained using ad hoc mathematical models and the outcome of the numerical simulations are managed with a GIS (Geographical Information System). Coastline evolution until the year 2100 is investigated and risk factor maps of the low-lying coastal areas are generated which account for the hazard of the expected event, and the land economic value and vulnerability.
Keywords: C60; 330; Numerical models; relative sea level rise; GIS simulation; risk analysis; Klimawandel; Überschwemmung; Simulation; Küstenregion; Italien (Nordost); Adriatisches Meer